Determinants of term premature rupture of membrane: case-control study in Saint Paul's Millennium Medical College Hospital, Addis Ababa, Ethiopia - Zelele daniel; Temesgen Tantu; Dereje Zewdu; Thomas Mekuria; Tsion Yehualashet; Muluken Gunta; Mekete Wondosen (BMC, 2023)
Abstract Background The term premature rupture of the membranes is the rupture of the membranes before the onset of labor beyond 37 weeks of gestation. Several factors, including obstetric, gynecologic, socioeconomic, and medical, are identified as potential risk factors. This clinical event has detrimental maternal and neonatal complications. Objectives This study aimed to investigate the determinants of the term premature rupture of the membranes in Ethiopia. Methods This institution-based unmatched case-control study was conducted on 246 women admitted to Saint Paul's hospital millennium medical college from October 2019 to January 2020 (82 cases and 164 controls). Data were collected using an interviewer-based questionnaire and data extraction tools, and data were entered using Epi data 3.1 and analyzed using SPSS 20. The association between independent variables and premature rupture of the membrane was estimated using an odds ratio with 95% confidence intervals and P-value < 0.05. Results Factors like a history of vaginal discharge (AOR 3.508;95% CI:1.595.7.716), place of Antenatal care follow-up (health center and Mercy Ethiopia) (AOR 5.174;95% CI:2.165,12.362), the previous history of rupture of membrane (AOR 9.955;95% CI:3.265,20.35), and gestational age (AOR 3.018;95% CI:1.338,6.811) were associated with term premature rupture of membrane. There were more maternal and neonatal complications, including puerperal sepsis, wound infection, anemia/PPH, a hospital stays of more than seven days, clinical amnionitis, neonatal hypoglycemia, early onset neonatal sepsis, and respiratory distress encountered by women who presented with premature rupture of membrane. Conclusion Proper screening, close monitoring, and early interventions in those mothers with identified risk factors would help to reduce its negative consequences. Moreover, the provision of continuous professional skill development and improving the quality of ANC service is needed.